2014
DOI: 10.1016/j.ceca.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of mitochondrial Ca2+ dynamics in astrocytes using cell-specific mitochondria-targeted GCaMP5G/6s: Mitochondrial Ca2+ uptake and cytosolic Ca2+ availability via the endoplasmic reticulum store

Abstract: Mitochondrial Ca2+ plays a critical physiological role in cellular energy metabolism and signaling, and its overload contributes to various pathological conditions including neuronal apoptotic death in neurological diseases. Live cell mitochondrial Ca2+ imaging is an important approach to understand mitochondrial Ca2+ dynamics. Recently developed GCaMP genetically-encoded Ca2+ indicators provide unique opportunity for high sensitivity/resolution and cell type-specific mitochondrial Ca2+ imaging. In the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 67 publications
1
39
0
1
Order By: Relevance
“…The latest GCaMP6 series developed by the Janelia GENIE Project performs as well as some organic Ca 2+ indicator dyes [24]. The properties of GCaMPs are further leveraged by targeting them to sub cellular compartments such as the plasma membrane [28-31], mitochondria [32-34] and endoplasmic reticulum [33, 35]. Ratiometric FRET based GECIs are also widely used and have been improved to tune Ca 2+ affinity to desirable levels [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest GCaMP6 series developed by the Janelia GENIE Project performs as well as some organic Ca 2+ indicator dyes [24]. The properties of GCaMPs are further leveraged by targeting them to sub cellular compartments such as the plasma membrane [28-31], mitochondria [32-34] and endoplasmic reticulum [33, 35]. Ratiometric FRET based GECIs are also widely used and have been improved to tune Ca 2+ affinity to desirable levels [36].…”
Section: Introductionmentioning
confidence: 99%
“…The data were indiscernible. Furthermore, GECIs have been deployed in several studies and no untoward effects have been reported [26, 28-32, 37, 38, 42-44, 47-55]. In future astrocyte studies, appropriate controls will still be needed.…”
Section: Introductionmentioning
confidence: 99%
“…Insert mitochondrial matrix (MM)-targeting sequence (mito-) ATGT CCGTCCTGAC GCCGCTGCTG CTGCGGGGCT TGACAGGCTC GGCCCGGCGG CTCCCAGTGC CGCGCGCCAA GATCCATTCG TTG (Rizzuto et al, 1995) in the backbone of AAV plasmid pZac2.1 containing astrocytic gfaABC 1 D promoter (Lee et al, 2008;Li et al, 2014;Xie et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Subclone GCaMP5G/6s or monomeric red fluorescence protein (mRFP) as a control into the cloning sites BamH I and Not 1 using PCR to obtain new expressing plasmids that can target transgene expression in mitochondria of astrocytes (Li et al, 2014) (Figure 2). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation